Effects of Compost Type and Rootstock Length on Fruit and Vegetable Seedlings Growth in the Nursery - Dody Priadi; Enung Sri Mulyaningsih (Biosaintifika: Journal of Biology & Biology Education, 2016)
The study was conducted to develop local fruit plants and to improve vegetable production at the Plant Germplasm Garden of RC for Biotechnology-LIPI. Carambola (Averrhoa carambola), durian (Durio zibethinus) and guava (Psidium guajava) were propagated vegetatively (grafting and budding) and were grown on the media containing grass compost (K-1), spent compost of paddy straw mushroom (K-2) or oyster mushroom (K-3) in combination with rootstock length of 45-55 cm (TB-1), 65-75 cm (TB-2) and 75-90 cm (TB-3). Tomato (Lycopersicum esculentum) and kangkung (Ipomoea reptans) were grown on the same media in the screen house. The highest survival rate of grafted durian (71.56%) was obtained from TB-3 grown on K-1 by budding technique. Meanwhile, the highest survival rate of carambola (68.89%) was obtained from TB-1 by grafting technique. The budding technique was not appropriate for guava (0 % of survival). Application of K-3 of 3 kgs on tomato plants resulted in the highest fresh weight, length, and diameter of the fruit, and the highest of plant height, total leaves, and biomass of kangkung. The study is expected to be applied to improve fruit plant growth and survival rate as well as a high production of organic vegetable.How to CitePriadi, D., Mulyaningsih, E. S. (2016). Effects of Compost Type and Rootstock Length on Fruit and Vegetable Seedlings Growth  in the Nursery. Biosaintifika: Journal of Biology Biology Education, 8(3), 301-307.